2014
DOI: 10.12659/aot.890934
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Among Older Adult Liver Transplantation Recipients in the Model of End Stage Liver Disease (MELD) Era

Abstract: Background Since 2002, the Model of End Stage Liver Disease (MELD) score has been the basis of the liver transplant (LT) allocation system. Among older adult LT recipients, short-term outcomes in the MELD era were comparable to the pre-MELD era, but long-term outcomes remain unclear. Material/Methods This is a retrospective cohort study using the UNOS data on patients age ≥50 years who underwent primary LT from February 27, 2002 until October 31, 2011. Results A total of 35,686 recipients met inclusion cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 53 publications
4
26
0
Order By: Relevance
“…Only one study did not include patients with a special MELD score, such as those with hepatocarcinoma 24 and one other 16 examined only cases involving patients aged over 50. …”
Section: Resultsmentioning
confidence: 99%
“…Only one study did not include patients with a special MELD score, such as those with hepatocarcinoma 24 and one other 16 examined only cases involving patients aged over 50. …”
Section: Resultsmentioning
confidence: 99%
“…Age: there is no current upper age limit for transplantation in the UK. Some studies demonstrate that long-term survival decreases with age above 60 (Collins et al 2000, Malinis et al 2014 mainly due to malignancy and infection whereas others found no differences in outcomes for appropriately selected older recipients (Bromley et al 1994, Garcia et al 2001, Cross et al 2007, Sonny et al 2015.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Older age has repeatedly been associated with worse pre- and post-transplant outcomes, 2,11,12 despite selection bias towards listing and transplanting only the “healthiest” of older patients. Candidates ≥65 years compared to <65 years experience a 35% increased odds of death or delisting for being too sick for transplant and 9% decreased odds of transplant (Table 1).…”
Section: Specific Conditions That Commonly Arise On the Wait-list Thamentioning
confidence: 99%
“…13 After transplant, older recipient age is associated with an increasing adjusted risk of graft loss (Table 1). 2 There exists a powerful interaction between age and laboratory MELD score at the time of transplant. At high MELD scores, defined as >28, liver transplant recipients between 65–69 years and ≥70 years (compared to <60 years) experienced significantly increased risk of graft loss (for 65–69 years: HR 1.4, 95%CI 1.2–1.7; for ≥70 years: HR 2.4, 95%CI 1.7–3.3) [p=0.01 for the interaction between age and laboratory MELD at transplant].…”
Section: Specific Conditions That Commonly Arise On the Wait-list Thamentioning
confidence: 99%
See 1 more Smart Citation